Factors Associated with Work-related Musculoskeletal Disorders Risk among Bamboo Craftsman in Mojorejo Village, Ponorogo Indonesia - Akbar Rahma, Ratih Andhika; Arifah, Dian Afif; Rosanti, Eka (Malaysian Journal of Medicine and Health Sciences, 2023)
Introduction: Work-related Musculoskeletal disorders (WMSDs) becomes the one of most-occupational problem and highly related to the individual and work factors. Eighty percent (80%) workers in the woven bamboo industry in Mojorejo Village dominated by middle aged workers (>40 years) that most of their producing activities are manually handled, without using machine or modern technology. Incompatibility work station, long working hours and repeated movement aggravated the WMSDs risk. This study aims to describe the WMSDs risk and determine its factors based on individual characteristics. Methods: There are 58 workers as respondents in this cross-sectional study. Data were collected and analyzed using quantitative method. Posture Exposure (PE) were measured using the QEC instrument. While the WMSDs risk were measured using PLIBEL. Individual factors (PE, Age, Working Period) related to WMSDs were analyzed using Multinomial Logistic Regression (95% CI). The Chi-square test were also used to compare PE rates among WMSDs risk levels. Results: Most respondents (48.3%) with 51-70% PE rate have a high level of WMSDs risk. While 27 % respondents with PE rate >70% have a very high level. The neck is the region most exposed to the WMSDs (score 15.5/very high level risk). PE rate is the only factor that significantly related to WMSDs risk (sig. = 0.043; Rsquare = 0.529; r =0.703). While the age and working period has no significant correlation (Sig = 0.859 and 0.851 respectively). Conclusion: Based on the result, immediate improvement required to be implemented. It is suggested to redesigned work stations adjusted to the workers posture and position. REFERENCES Daneshmandi H, Choobineh A, Ghaem H, Alhamd M, Fakherpour A. The effect of musculoskeletal problems on fatigue and productivity of office personnel: a cross-sectional study. J Prev Med Hyg. 2017;58:E252-E258.[Google Scholar] [PMC free article] [Pubmed] Yelin E, Felts W. A summary of the impact of musculoskeletal conditions in the united states. Arthritis & Rheumatism. 1990;33:750-5. https://doi.org/10.1002/art.1780330520[Google Scholar][Pubmed] Summers K, Jinnett K, Bevan S. Musculoskeletal disorders, workforce health and productivity in the United States. The center for workforced health and performance. London: Lancaster university. 2015;.[Google Scholar] Arifah D, Basri A. Stretching exercise to reduce musculoskeletal pain among x bakery’s workers. International Journal of Public Health Science (IJPHS). 2021;10:544. https://doi.org/10.11591/ijphs.v10i3.20877[Google Scholar] Da Costa B, Vieira E. Risk factors for work-related musculoskeletal disorders: a systematic review of recent longitudinal studies. American Journal of Industrial Medicine. 2010;53:285-323. https://doi.org/10.1002/ajim.20750[Google Scholar][Pubmed] Juul-Kristensen B, Hansson G, Fallentin N, Andersen J, Ekdahl C. Assessment of work postures and movements using a video-based observation method and direct technical measurements. Applied Ergonomics. 2001;32:517-24. https://doi.org/10.1016/s0003-6870(01)00017-5[Google Scholar][Pubmed][Crossref] WHO and others. Preventing musculoskeletal disorders in the workplace. Protecting workers 'Health series no. 5'. 2003;.[Google Scholar] Cimelli S, Curran S. Influence of turnout on foot posture and its relationship to overuse musculoskeletal injury in professional contemporary dancers: a preliminary investigation. J Am Podiatr Med Assoc. 2012;102:25-33. https://doi.org/10.7547/1020025[<a href="https://scholar.google.com/scholar_lookup?title=Influence+of+turnout+on+foot+posture+and+its+relationship+to+overuse+musculoskeletal+injury+in+professional+contemporary+dancers%3A+a+preliminary+investigation&btnG=">Google Scholar][Pubmed] Anghel M, Argeanu V, Talpo C, Lungeanu D. Musculoskeletal disorders (MSDS) consequences of prolonged static postures. J Exper Med Surg Res. 2007;4:167-72.[Google Scholar] Siong V, Azlis-Sani J, Nor NM, Yunos MAM, Boudeville J, Ismail S. Ergonomic assessment in small and medium enterprises (SMEs). Journal of Physics Conference Series. 2018;1049:12065. https://doi.org/10.1088/1742-6596/1049/1/012065[Google Scholar] Fahmi F, Koster S. Creative Industries and Regional Productivity Growth in the Developing Economy: Evidence from Indonesia. Growth and Change. 2017;48:805-30. https://doi.org/10.1111/grow.12212[Google Scholar] Kemenperin. Kontribusi PDB Ekonomi Kreatif Ditargetkan 7.5%. Ministry of Industry: Contributor of Bruto Domestic Product to Creative Economy. 2015;. Budidarsono S, Susanti A, Zoomers A. Oil Palm Plantations in Indonesia: The Implications for Migration, Settlement/Resettlement and Local Economic Development. Biofuels - Economy, Environment and Sustainability. 2013;:173-93.[Google Scholar] Sofiana Y, Sylvia C, Purbasari M. Potential of Bamboo as Material for Furniture in Rural Area in Indonesia. Advanced Science Letters. 2017;23:263-6. https://doi.org/10.1166/asl.2017.7153[Google Scholar] Prihatini J. The Challenges of Small Industry of Woven Bamboo Craftsmen to Meet Industrial 4.0 in District of Majalengka, West Java, Indonesia. International Conference on Environmental Awareness for Sustainable Development in conjunction with International Conference on Challenge and Opportunities Sustainable Environmental Development, ICEASD & ICCOSED. 2019. 2019. 1-2 April 2019, 2019;:378. https://doi.org/10.4108/eai.1-4-2019.2287242[Google Scholar] Diannita R, Mohammad Muslih, Neri Wijayanti, Umma Fatayati. Participatory Rural Appraisal (PRA) For The Development Of Safe Weaving Bamboo Production Through Community Empowerment To Improve Health And Safety Of Bamboo Weaving Craftsmen In Mojorejo, Ponorogo,East Java, Indonesia. International Journal Of Community Service. 2021. 2021;1:243-52. https://doi.org/10.51601/ijcs.v1i3.44[<a href="https://scholar.google.com/scholar_lookup?title=Participatory+Rural+Appraisal+%28PRA%29+For+The+Development+Of+Safe+Weaving+Bamboo+Production+Through+Community+Empowerment+To+Improve+Health+And+Safety+Of+Bamboo+Weaving+Craftsmen+In+Mojorejo%2C+Ponorogo%2CEast+Java%2C+Indonesia&btnG=">Google Scholar] Pourmemari M, Heliövaara M, Viikari-Juntura E, Shiri R. Carpal tunnel release: Lifetime prevalence, annual incidence, and risk factors. Muscle & Nerve. 2018;58:497-502. https://doi.org/10.1002/mus.26145[Google Scholar][Pubmed] Baldasseroni A, Tartaglia R, Carnevale F. Rischio di sindrome del tunnel carpale in alcune attività lavorative (The risk of the carpal tunnel syndrome in some work activities). Med Lav. 1995;86:341-51.[Google Scholar] Hasegawa T, Katsuhira J, Oka H, Fujii T, Matsudaira K. Association of low back load with low back pain during static standing. PLOS ONE. 2018. 2018 Dec 18;13:e0208877. https://doi.org/10.1371/journal.pone.0208877[Google Scholar][PMC free article] [Pubmed] Gheno R, Cepparo J, Rosca C, Cotten A. Musculoskeletal Disorders in the Elderly. Journal of Clinical Imaging Science. 2012;2:39. https://doi.org/10.4103/2156-7514.99151[Google Scholar] [PMC free article] [Pubmed] Dinar A, Susilowati I, Azwar A, Indriyani K, Wirawan M. Analysis of Ergonomic Risk Factors in Relation to Musculoskeletal Disorder Symptoms in Office Workers. KnE Life Sciences. 2018;4:16. https://doi.org/10.18502/kls.v4i5.2536[Google Scholar] Potthoff R. Equivalent Sample Size' and 'Equivalent Degrees of Freedom' Refinements for Inference Using Survey Weights Under Superpopulation Models. Journal of the American Statistical Association. 1992;87:383-96. https://doi.org/10.2307/2290269.[Google Scholar] Nunnally J, Bernstein I. Psychometric theory (3rd edition). New York: McGraw-Hill,. 1994;. Wijayati E. RISIKO LAMA MEMPERTAHANKAN POSTUR KERJA TERHADAP KELUHAN SUBYEKTIF NYERI LEHER PADA PEKERJA INDUSTRI KERAJINAN KULIT DI SELOSARI. JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan). 2020;5:56. https://doi.org/10.30829/jumantik.v5i1.5891[Google Scholar] Schibye B, Skov T, Ekner D, Christiansen J, Sjøgaard G. Musculoskeletal symptoms among sewing machine operators. Scandinavian Journal of Work, Environment & Health. 1995;21:427-34. https://doi.org/10.5271/sjweh.58[Google Scholar][Pubmed] Bernard B, Others. Musculoskeletal disorders (MSDs) and workplace factors: A critical review of epidemiologic evidence for work-related musculoskeletal disorders of the neck, upper extremity, and low back. US Department of Health and Human Services,. National Institute for Occupational Safety and Health (NIOSH), Cincinatti, OH. 1997;.[<a href="https://scholar.google.com/scholar_lookup?title=Musculoskeletal+disorders+%28MSDs%29+and+workplace+factors%3A+A+critical+review+of+epidemiologic+evidence+for+work-related+musculoskeletal+disorders+of+the+neck%2C+upper+extremity%2C+and+low+back.+US+Department+of+Health+and+Human+Services&btnG=">Google Scholar] Sriagustini I, Supriyani T. A Analisis Bahaya pada Pengrajin Anyaman Bambu. Faletehan Health Journal. 2021;8:223-30.[Google Scholar] Nugroho AS. PERBAIKAN POSTUR KERJA UNTUK MENGURANGI KELUHAN MUSKULOSKELETAL PADA PROSES PENGANYAMAN ROTAN DI UKM ANGGUN ROTAN. 2019;.[Google Scholar] Carter J, Banister E. Musculoskeletal problems in VDT work: a review. Ergonomics. 1994;37:1623-48. https://doi.org/10.1080/00140139408964941[Google Scholar][Pubmed] Gearhart Jr. R, Goss F, Lagally K, Jakicic J, Gallagher J, Gallagher K, Robertson R. Ratings of Perceived Exertion in Active Muscle During High-Intensity and Low-Intensity Resistance Exercise. The Journal of Strength and Conditioning Research. 2002;16:87.[Google Scholar][Pubmed] Hogan DM, Greiner B, O'sullivan L. The effect of manual handling training on achieving training transfer, employee's behaviour change and subsequent reduction of work-related musculoskeletal disorders: a systematic review. Ergonomics. 2014;57:93-107. https://doi.org/10.1080/00140139.2013.862307[<a href="https://scholar.google.com/scholar_lookup?title=The+effect+of+manual+handling+training+on+achieving+training+transfer%2C+employee%27s+behaviour+change+and+subsequent+reduction+of+work-related+musculoskeletal+disorders%3A+a+systematic+review&btnG=">Google Scholar][Pubmed] Jagannath M, Balasubramanian V. Assessment of early onset of driver fatigue using multimodal fatigue measures in a static simulator. Applied Ergonomics. 2014;45:1140-7. https://doi.org/10.1016/j.apergo.2014.02.001[Google Scholar][Pubmed] Hostens I, Ramon H. Assessment of muscle fatigue in low level monotonous task performance during car driving. Journal of Electromyography and Kinesiology. 2005;15:266-74. https://doi.org/10.1016/j.jelekin.2004.08.002[Google Scholar][Pubmed][Crossref] Arifah D, Andarini Y, Dianita R. Occupational Fatigue Based on Work Shift Among Medical Workers at Harjono S Hospital. Jurnal Ilmu Kesehatan Masyarakat. 2019;10:199-206. https://doi.org/10.26553/jikm.2019.10.3.199-206[Google Scholar]